2013
DOI: 10.1590/s0100-204x2013000700006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of sweet oranges with the D4E1 gene driven by the AtPP2 promoter

Abstract: -The objective of this work was to produce transgenic 'Pêra' and 'Valência' sweet orange plants using the D4E1 gene driven by the Arabidopsis thaliana phloem protein (AtPP2) promoter and to quantify transgene expression in different transformation events. Genetic transformation experiments were carried out with epicotyl segments co-cultivated with Agrobacterium tumefaciens. Six plants from 'Pêra' sweet orange and seven plants from 'Valência' sweet orange were confirmed as different transgenic events by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
3
0
6
Order By: Relevance
“…was\10 lM. We found that D4E1 was most effective against A. flavus in vitro, as previously reported (De Lucca et al 1998), but the transient expression of this peptide in tobacco plants induced severe necrosis, in contrast to earlier reports (Attílio et al 2013;Cary et al 2000;Mentag et al 2003;Rajasekaran et al 2005). We therefore tested the activity of thanatin against A. flavus and A. parasiticus and for the first time demonstrated its antifungal properties against both species in vitro and against A. flavus in planta.…”
Section: Discussionsupporting
confidence: 54%
“…was\10 lM. We found that D4E1 was most effective against A. flavus in vitro, as previously reported (De Lucca et al 1998), but the transient expression of this peptide in tobacco plants induced severe necrosis, in contrast to earlier reports (Attílio et al 2013;Cary et al 2000;Mentag et al 2003;Rajasekaran et al 2005). We therefore tested the activity of thanatin against A. flavus and A. parasiticus and for the first time demonstrated its antifungal properties against both species in vitro and against A. flavus in planta.…”
Section: Discussionsupporting
confidence: 54%
“…The AtPP2 promoter was used to govern transcription of a gene for synthetic antimicrobial peptide D4E1 to control the HLB-associated bacteria in citrus (Attílio et al 2013 ). Among the main diseases, citrus variegated chlorosis (CVC), caused by Xylella fastidiosa , is characterized by colonization and clogging of the xylem vessels.…”
Section: Sweet Orangementioning
confidence: 99%
“…However, strong transgene expression without tissue discrimination can result in unnecessary energy expenditure by the plant and possible side effects due to putatively harmful transgene products (ALTPETER et al, 2005;WANG et al, 2005;ZHAO et al, 2004). One method to fine tune transgene expression is to use tissue-specific promoters induced by pathogens or abiotic stresses (BARBOSA-MENDES et al, 2009;DUTT et al, 2012;MIYATA et al, 2012;BENYON et al, 2013;ATTÍLIO et al, 2013;ZOU et al, 2014).…”
Section: Introductionmentioning
confidence: 99%